Curcumin prevents high-fat diet-induced hepatic steatosis in ApoE−/− mice by improving intestinal barrier function and reducing endotoxin and liver TLR4/NF-κB inflammation - Dan Feng; Jun Zou; Dongfang Su; Haiyan Mai; Shanshan Zhang; Peiyang Li; Xiumei Zheng (Nutrition & Metabolism, 2019)
Abstract Background Non-alcoholic fatty liver disease (NAFLD) is the most common chronic liver disease and has become a public health concern worldwide. The hallmark of NAFLD is hepatic steatosis. Therefore, there is an urgent need to develop new therapeutic strategies that are efficacious and have minimal side effects in hepatic steatosis and NAFLD treatment. The present study aimed to investigate the effect of dietary supplement of curcumin on high-fat diet (HFD)-induced hepatic steatosis and the underlying mechanism. Methods ApoE−/− mice were fed a normal diet, high-fat diet (HFD) or HFD supplemented with curcumin (0.1% w/w) for 16 weeks. Body and liver weight, blood biochemical. parameters, and liver lipids were measured. Intestinal permeability, hepatic steatosis and mRNA and protein expressions of TLR4-related inflammatory signaling molecule were analyzed. Results The administration of curcumin significantly prevented HFD-induced body weight gain and reduced liver weight. Curcumin attenuated hepatic steatosis along with improved serum lipid profile. Moreover, curcumin up-regulated the expression of intestinal tight junction protein zonula occluden-1 and occludin, which further improved gut barrier dysfunction and reduced circulating lipopolysaccharide levels. Curcumin also markedly down-regulated the protein expression of hepatic TLR4 and myeloid differentiation factor 88 (MyD88), inhibited p65 nuclear translocation and DNA binding activity of nuclear factor-κB (NF-κB) in the liver. In addition, the mRNA expression of hepatic tumour necrosis factor-α (TNF-α) and interleukin-1β (IL-1β) as well as the plasma levels of TNF-α and IL-1β were also lowered by curcumin treatment. Conclusion These results indicated that curcumin protects against HFD-induced hepatic steatosis by improving intestinal barrier function and reducing endotoxin and liver TLR4/NF-κB inflammation. The ability of curcumin to inhibit hepatic steatosis portrayed its potential as effective dietry intervention for NAFLD prevention.